Femina - Aziz M. Osman; Badaruddin Haji Azmi (Kuala Lumpur : Cipta Video Sdn. Bhd., 1994)
Mengisahkan tentang keadaan dan pergolakan wanita yang berkerja
Pelakon: Erma Fatima, Eman Manan, Susan Lankester
Keywords: Women in development -- Malaysia -- Drama